Karst-environments of the southeastern Yucatan Peninsula: Hotspots for modern freshwater microbialites - Alfredo Yanez-Montalvo; Bernardo Águila; Arit S. de León-Lorenzana; Arturo Bayona; Nuria Torrescano-Valle; Pavel Popoca; Luisa I. Falcón (PLoS ONE, 2025)
Modern microbialites are sedimentary structures that offer a window into Earth’s geologic history and the intricate interplay between geology and microorganisms. Microbialites are formed by the interaction between microbial communities and the environment leading to mineral precipitation. This study provides a comprehensive analysis of the bacterial and archaeal composition (using the V4 region of the 16S rRNA), along with mineralogy, geochemistry, and hydrogeochemical characterizations of microbialites of five aquatic systems (Bacalar, Muyil, Chichancanab, Azul and Cenote Azul) in southeastern Yucatan Peninsula, México. Dominant taxa were distributed within Pseudomonadota, Cyanobacteriota, Bacillota, Bacteroidota, Chloroflexota, and Planctomycetota, while NB1-j, Myxoscoccota, Verrucomicrobiota, Acidobacteriota, and Crenarchaeota (Archaea) were less abundant. Microbialites from Cenote Azul, a deep sinkhole, were the most different and biodiverse. Notably, potential new families of Cyanobacteriota were observed in all microbialite sites. The primary mineral constituents in microbialites were calcite, magnesian calcite, and gypsum. Hydrogeochemical conditions differed among sites despite their hydrological connectivity. Overall, the karstic ecosystem, hydrogeochemical conditions, tropical climate, and shallow coastal landscapes have favored the occurrence of microbialites in the Yucatan Peninsula, a hotspot region for the formation of these communities. However, their safeguarding becomes crucial, emphasizing the urgency of our role in environmental conservation, in the face of challenging conditions associated with climate change and increased anthropogenic activities detrimental to the environment.